Biodegradable Active Packaging Enriched with Essential Oils for Enhancing the Shelf Life of Strawberries - Magdaléna Rusková; Alena Opálková Šišková; Katarína Mosnáčková; Custódia Gago; Adriana Guerreiro; Mária Bučková; Andrea Puškárová; Domenico Pangallo; Maria Dulce Antunes (MDPI AG, 2023)
The strawberry (Fragaria ananassa) is a nutrient-rich fruit with high content of health-beneficial compounds. However, strawberries are susceptible to mechanical damage and microbiological contamination which can cause changes in fruit sensory properties. These changes consequently effect on ripening and shelf life of the strawberry. In recent years, essential oils (EOs) have been famous for their antimicrobial and antioxidant properties and are promising ecological alternatives to chemical antimicrobial substances. Nowadays, active packaging is one of several techniques developed for slowing down the metabolic processes of fresh fruits. Poly(lactic acid) (PLA) is one of the several polymers suitable for encapsulation EOs, whereas at the same time represent non-toxic, biodegradable, and compostable polymer derived from renewable resources. Suitable packaging prolongs the shelf life of fruit, keeps the products at the highest possible nutrition level, improves quality, and attracts customer attention. In the current study, we encapsulated EOs (lemongrass and oregano) into a PLA and poly(3-hydroxybutyrate) (PHB) packaging film and explored their antimicrobial and antioxidant properties. Moreover, biochemical and quality parameters for strawberry preservation and shelf-life extension were also assessed. Our tested active packaging film with EOs was proven to be useful for postharvest quality maintenance and shelf-life extension of strawberries, with PLA/PHB/ATBC + 5% lemongrass EO being slightly better than PLA/PHB/ATBC + 5% oregano EO.